Environmental problems white salmon populations in pollution of the Volga-Caspian basin - A. V. Ampleeva; O. V. Lojnichenko (Юг России: экология, развитие)
Uncontrolled industrial effluents into water bodies and the use of different types of herbicides and pesticides in agriculture has led to widespread pollution of fishery waters.